The Impact of GLP-1 Receptor Agonists on Physical Functioning and Quality of Life in Adults with Obesity: A Narrative Review - Łupina-Romaniuk, Marcela; Kołodziejczyk , Julia; Pietrzak, Maria; Chawryło , Aneta; Piecuch , Dominika; Oleksińska , Karolina; Świetlicka , Gabriela; Pietraś , Paulina; Stolarczyk , Michał; Pracoń , Karolina (Quality in Sport, 2026)
Background. Obesity is a chronic disease associated with impaired physical functioning and reduced quality of life. GLP-1 receptor agonists have emerged as an effective therapeutic option for weight reduction and may also provide additional benefits in these areas. Aim. The aim of this study was to present the current state of knowledge on the effects of GLP-1 receptor agonists on physical functioning and quality of life in adults with obesity. Material and methods. This study is a narrative literature review. The analysis was based primarily on publications identified in PubMed, as well as on full-text articles available in PubMed Central (PMC) and on publishers’ websites. Publications from 2021–2025 concerning adults with overweight or obesity were primarily included. Results. Available evidence indicates that GLP-1 receptor agonists, particularly semaglutide, effectively reduce body weight and may also have favorable effects on physical functioning and quality of life. The most promising findings concern improvements in patient-reported physical functioning, limitations in daily activities, and weight- and health-related quality of life. Limitations of therapy include adverse effects, the possibility of weight regain after treatment discontinuation, high cost, and limited availability of these agents. Conclusions. The evaluation of the efficacy of GLP-1 receptor agonists should not be limited solely to body weight reduction, but should also take into account the impact of therapy on physical functioning and quality of life.